Reliability and safety of a new upper cervical spine injury treatment algorithm - Joaquim, Andrei Fernandes; Brock, Roger Schmidt; Guirado, Vinicius Monteiro de Paula; Sandon, Luis Henrique; Silva, Otávio Turolo da; Taricco, Mário Augusto; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos de Neuro-Psiquiatria, 2017)
In the present study, we evaluated the reliability and safety of a new upper cervical spine injury treatment algorithm to help in the selection of the best treatment modality for these injuries. Methods Thirty cases, previously treated according to the new algorithm, were presented to four spine surgeons who were questioned about their personal suggestion for treatment, and the treatment suggested according to the application of the algorithm. After four weeks, the same questions were asked again to evaluate reliability (intra- and inter-observer) using the Kappa index.Results The reliability of the treatment suggested by applying the algorithm was superior to the reliability of the surgeons’ personal suggestion for treatment. When applying the upper cervical spine injury treatment algorithm, an agreement with the treatment actually performed was obtained in more than 89% of the cases.Conclusion The system is safe and reliable for treating traumatic upper cervical spine injuries. The algorithm can be used to help surgeons in the decision between conservative versus surgical treatment of these injuries.
Keywords: spinal injuries; spinal cord injuries; therapeutics; classification